2004
DOI: 10.1111/j.1471-4159.2004.02372.x
|View full text |Cite
|
Sign up to set email alerts
|

Distinct aggregation and cell death patterns among different types of primary neurons induced by mutant huntingtin protein

Abstract: Aggregation of disease proteins is believed to be a central event in the pathology of polyglutamine diseases, whereas the relationship between aggregation and neuronal death remains controversial. We investigated this question by expressing mutant huntingtin (htt) with a defective adenovirus in different types of neurons prepared from rat cerebral cortex, striatum or cerebellum. The distribution pattern of inclusions is not identical among different types of primary neurons. On day 2 after infection, cytoplasm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
32
2

Year Published

2006
2006
2023
2023

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 34 publications
(36 citation statements)
references
References 60 publications
2
32
2
Order By: Relevance
“…Although several studies have found aggregates to be associated with cell death, [8][9][10] others have found no correlation between aggregation of mutant htt and cellular toxicity. 11,12,13 A provocative study has found that the presence of inclusion bodies containing mutant htt may actually predict lower risk of cell death in primary neurons. 14 Indeed, it has been DZNE, German Center for Neurodegenerative Diseases, suggested that htt aggregates may represent a molecular sink for soluble toxic htt forms.…”
mentioning
confidence: 99%
“…Although several studies have found aggregates to be associated with cell death, [8][9][10] others have found no correlation between aggregation of mutant htt and cellular toxicity. 11,12,13 A provocative study has found that the presence of inclusion bodies containing mutant htt may actually predict lower risk of cell death in primary neurons. 14 Indeed, it has been DZNE, German Center for Neurodegenerative Diseases, suggested that htt aggregates may represent a molecular sink for soluble toxic htt forms.…”
mentioning
confidence: 99%
“…Several studies have suggested that not all forms of aggregates may be toxic [70][71][72]. In fact, large (amyloidic) aggregates that entrap these various key cellular elements have been found to be protective in certain systems and under certain conditions [70][71][72][73][74][75]. It has thus been proposed that smaller (amorphic) oligomeric and/or heteromeric species are more toxic as they are capable of freely moving around in the cellular milieu and perturb various neuronal functions.…”
Section: The Role Of Hspbs In Neurodegenerative and Neuromuscular Dismentioning
confidence: 99%
“…Many classic HD models express exon 1 of the mutant protein Jackson et al 1998;Krobitsch and Lindquist 2000;Tagawa et al 2004), which is capable of forming inclusions postulated to play a role in HD pathology Becher et al 1998). To determine whether the in vivo subcellular localization of the 81-aa exon 1 fragment of pathogenic human Htt (HttQ96-GFP) differs from that of the 588-aa pathogenic Htt fragment in our Drosophila model, HttQ96-GFP-expressing third instar larvae were imaged using confocal microscopy.…”
Section: Exon 1 Of Pathogenic Htt Forms Cytoplasmic and Neuritic Aggrmentioning
confidence: 99%